Rancang Bangun Model Turbin Tesla Dengan Variasi Tekanan - Miswar, Ahmad; Ramadhani, Nurul; Hamzah, Nur; Suryanto, Suryanto (Jurnal Teknik Mesin Sinergi, 2024)
Electric energy is one of the essential aspects required in daily life. One of the most commonly used sources of electricity today is the steam power plant. However, the energy from this steam requires a special device to be converted into mechanical energy. The turbine used in this design is a steam turbine.The purpose of this design is to create a model of the Tesla turbine as a steam turbine, to determine the rotational speed generated by the Tesla turbine when subjected to varying steam pressures, and to determine the power generated by the generator when the Tesla turbine is subjected to varying steam pressures.The test results showed the highest rotation speed was 681 rpm, condensate water level was 1430 ml, current was 0.5 A, and voltage was 13 V with a constant load of a 12-watt lamp. The highest analysis data obtained were generator power of 0.0065 kW, mass flow rate of 0.02383 kg/s, input power of 24.162 kW, and system efficiency of 0.036%.